V-Gel® Guided Endotracheal Intubation in Rabbits - Fusco, Alessandra; Douglas, Hope; Barba, Adriana; Hopster, Klaus; Stefanovski, Darko; Sinder, Benjamin; Cahill, Patrick J.; Snyder, Brian; Schaer, Thomas P. (Frontiers in Veterinary Science, 2021)
Background: General anesthesia in rabbits is associated with higher morbidity and mortality relative to other mammalian species commonly anesthetized. Unique challenges related to endotracheal intubation (ETI) in rabbits contribute to this risk. Objective: To improve the safety of ETI in rabbits, we developed two new ETI methods using a supraglottic airway device (v-gel®) to facilitate ETI and compared them to traditional “blind” technique. We hypothesized that relative to blind ETI, v-gel® guided ETI provides more successful placement of the endotracheal tube (ETT) in a shorter time. Outcomes included number of intubation attempts, time for achievement of ETI, endoscopic findings and serial arterial blood gas (ABG) analysis. Study Design: Prospective, randomized, crossover study. Methods: Ten female, New Zealand White rabbits aged 1 to 2 years old, weighing 4.3±0.4 kg, were anesthetized four times. Each time, ETI was performed with one of the following techniques: Method 1: v-gel® guided, polypropylene catheter facilitated, intubation using a cuffed ETT; Method 2: v-gel® guided intubation using an uncuffed ETT directly inserted through the device airway channel; Method 3&4: Blind intubation with uncuffed or cuffed ETT. Upper airway endoscopy was performed before intubation attempts and after extubation. Serial ABG analysis was performed during the peri-intubation process. Results: V-gel® guided techniques allowed successful ETI on the initial attempt for 9/10 subjects using Method 1 and 10/10 using Method 2. Relative to the v-gel® guided techniques, the blind techniques required more intubation attempts. A median of 2 attempts (range 1-4, p < 0.007) were required for the uncuffed ETT, and a median of 4 (range 1-4, p < 0.001) attempts were performed for the cuffed ETT. The time to perform successful ETI was positively correlated with the number of attempts (ρ = 0.82), while successful ETI was negatively correlated with number of attempts (ρ = - 0.82). Endoscopic findings showed mild to moderate laryngeal trauma. In the absence of oxygen supplementation, ABG analysis demonstrated low PaO2, while PaCO2 remained consistent. Conclusions: Facilitated ETI using the v-gel® guided techniques allows for the rapid establishment of a secure airway to provide ventilatory support for rabbits undergoing general anesthesia.